Potential of the LASH model for water resources management in data-scarce basins: a case study of the Fragata River basin, southern Brazil. Issue 14 (25th October 2016) - Beskow, Samuel; Timm, Luis Carlos; Tavares, Vitor Emanuel Quevedo; Caldeira, Tamara Leitzke; Aquino, Leandro Sanzi
ABSTRACT: The objective of this study was to evaluate, based on a data-scarce basin in southern Brazil, the potential of the Lavras Simulation of Hydrology (LASH) model for estimating daily streamflows, annual streamflow indicators and the flow–duration curve. It was also used to simulate the different runoff components and their consistency with the basin physiographical characteristics. The statistical measures indicated that LASH can be considered suitable according to widely used classifications and when compared with other studies involving hydrological models. LASH also showed satisfactory results for annual indicators, especially for maximum and average annual streamflows, as well as for the flow–duration curve. It was found that the model was consistent with the basin characteristics when simulating runoff components. The results obtained in this study allowed us to conclude that the LASH model has the potential to aid practitioners in water resources management of basins with scarce data and similar soil and land-use conditions.Editor A. Castellarin;Associate editor Y. Gyasi-Agyei